2019
DOI: 10.1097/mpg.0000000000002397
|View full text |Cite
|
Sign up to set email alerts
|

Feeding the Late and Moderately Preterm Infant

Abstract: Objectives-This report presents 2008 data on U.S. births according to a wide variety of characteristics. Data are presented for maternal demographic characteristics including age, live-birth order, race and Hispanic origin, marital status, attendant at birth, method of delivery, and infant characteristics (period of gestation, birthweight, and multiple births). Birth and fertility rates by age, live-birth order, race and Hispanic origin, and marital status also are presented. Selected data by mother's state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 127 publications
1
107
1
7
Order By: Relevance
“…Neither infants with BPD nor infants exclusively fed with formula milk showed differences with and without developmental care. Even though the European Society for Pediatric Gastroenterology, Hepatology and Nutrition Committee on Nutrition recommends breast milk feeding in their position paper [ 33 ], there is no guideline for feeding preterm infants. Therefore, the choice of feeding mode was based on the SOP of the NICU in Rostock.…”
Section: Discussionmentioning
confidence: 99%
“…Neither infants with BPD nor infants exclusively fed with formula milk showed differences with and without developmental care. Even though the European Society for Pediatric Gastroenterology, Hepatology and Nutrition Committee on Nutrition recommends breast milk feeding in their position paper [ 33 ], there is no guideline for feeding preterm infants. Therefore, the choice of feeding mode was based on the SOP of the NICU in Rostock.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the lack of consistency in answering the questionnaires influenced the validity of the findings. A major limitation is the lack of data on LPT health characteristics including hyperbilirubinemia, which may impact on initiation of breastfeeding and maternal depression 7,14 . Considering the levels of worries and stress reported by LPT mothers, it is interesting that the results did not show differences in parenting stress measures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mothers with LPT infants have showed that they are less likely to initiate, and sustain, breastfeeding compared with mothers of term infants 3‐5 and even the mothers of more preterm infants 6 . Thus, there is a need for better lactation support for LPT infant‐mother dyads 7 …”
Section: Introductionmentioning
confidence: 99%
“…The position paper by the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) recommend an elemental iron intake of 1-2 mg/kg/day for all premature infants with a birth weight less than 2500 g and of 2-3 mg/kg/day for those weighing less than 2000 g [92]. Similarly, the Committee on Nutrition of the AAP suggests a daily iron supplementation of 2 mg/kg for all breastfed preterm infants, from 1 to 12 months of age [93].…”
Section: Enteral Iron Supplementationmentioning
confidence: 99%